Organochlorine Pesticide Residues in Human Fat in Great Britain. Issue 5611 (20th July 1968) - Abbott, D. C.; Goulding, R.; Tatton, J. O'G.
Abstract : In order to assess the trend in the body load of organochlorine pesticide residues in Great Britain, between July 1965 and June 1967 samples of fat were taken during routine necropsies on 247 subjects over 3 years old and on 44 stillborn or premature babies and infants below the age of 3. The levels of the three main pesticides, B.H.C., dieldrin, and D.D.T., were lower than those found in an earlier survey carried out in 1963 and 1964. No marked differences were observed in levels throughout Britain, but the levels in man were higher than those in women. Britain compares favourably with other countries in which similar surveys have been done.